COMPLEX APPROACH TO EVALUATION OF THE EFFICIENCY OF CREDIT-INVESTMENT ACTIVITIES OF BANKS - Шльончак, Василь (Socio-economic relations in the digital society, 2019)
We have conducted assessment of efficiency of credit and investment bank activities based on implementation of author developed complex approach. To obtain higher accuracy data the selection has been performed. The sample has been formed including representatives of diff erent banking groups based on the banking effi ciency ratios and the influence banks have on banking system activity. To be applied withing integral assessment method set of improved ratios of assessment of credit and investment banking effi ciency was developed. Taking into consideration analysis’ results the advantages and drawbacks of banking in Ukraine were defi ned. Based on complex approach implementation results’ advices on banking efficiency improvement were provided.